Kerjasama pemerintah dengan badan usaha: Harapan baru pembangunan infrastruktur di Indonesia - Al Hazmi, Raldin Alif (Journal of Law, Administration, and Social Science, 2024)
It takes Rp6,445 trillion to build infrastructure in Indonesia. As a form of support for infrastructure development, the state budget cannot fully finance it, so cooperation with the private sector is needed. PPP is the main solution in implementing infrastructure development in Indonesia. PPP is a creative financing and is expected to reduce the fiscal pressure of the state budget. However, PPP does not always run smoothly, this is due to the many obstacles in the implementation of infrastructure development with the PPP scheme. This research uses a qualitative approach based on case studies of infrastructure development in Indonesia which focuses on PPP in the waste management and education sectors. In the waste management and education sectors, it is still found that the obstacle to PPP is the lack of attractive investment in the sector according to investors. In addition, there is a lack of understanding of local governments in implementing PPP programs. Another thing is also closely related to corrupt practices that exist in the infrastructure development contract process which raises its own risks. Mapping the keys to successful PPP implementation include better contract reform, government commitment and government transparency. It is expected that the Government of Indonesia can commit to infrastructure development and transparency so that public support and trust in the government will arise. Dibutuhkan dana sebesar Rp6.445 triliun untuk membangun infrastruktur di Indonesia. Sebagai bentuk dukungan pembangunan infrastruktur, APBN tidak sepenuhnya dapat membiayainya sehingga diperlukan kerjasama dengan pihak swasta. KPBU menjadi solusi utama dalam pelaksanaan pembangunan infrastruktur di Indonesia. KPBU menjadi pembiayaan kreatif dan diharapkan dapat menurunkan tekanan fiskal APBN. Namun tidak selamanya KPBU berjalan dengan lancar, hal ini dikarenakan banyaknya hambatan dalam pelaksanaan pembangunan infrastruktur dengan skema KPBU. Penelitian ini menggunakan pendekatan kualitatif berdasarkan studi kasus pembangunan infrastruktur di Indonesia yang berfokus pada KPBU di sektor pengeloaan sampah dan Pendidikan. Dalam sektor pengelolaan sampah dan pendidikan masih ditemukan bahwa hambatan KPBU adalah kurang menariknya investasi di sektor tersebut menurut investor. Selain itu adanya minimnya pemahaman pemerintah daerah dalam melaksanakan program KPBU. Hal lain juga erat kaitannya dengan praktik korupsi yang ada dalam proses kontrak pembangunan infrastruktur yang memunculkan risiko tersendiri. Pemetaan kunci sukses pelaksanaan KPBU antara lain dengan pembenahaan kontrak yang lebih baik, komitmen pemerintah serta transparansi pemerintah. Diharapkan Pemerintah Indonesia dapat melakukan komitmen dalam pembangunan infrastruktur serta transparansi sehingga timbul dukungan dan kepercayaan masyarakat terhadap pemerintah.